Fine-needle aspiration cytology of adrenal myelolipoma: case report and review of the literature - Settakorn J. (2014)
Adrenal myelolipoma is a rare nonfunctioning tumor consisting histologically of an admixture of adipose tissue and extramedullary hemopoietic elements within the adrenal glands. Less than 300 cases have been reported in the literature and only 15 case reports have described cytological findings of this tumor obtained by fine-needle aspiration (FNA). We report a case of a 48-year-old male who had had anaplastic large cell carcinoma of the right lung. The left adrenal mass was encountered during a staging workup that led to a clinical suspicion of metastatic disease to the adrenal gland. FNA under computed tomography (CT) guidance was performed obtaining cytological material from which diagnosis of myelolipoma was made. The findings reemphasized an important role of FNA in investigation of adrenal mass. The literature on FNA cytology of adrenal myelolipoma is reviewed. Diagn. Cytopathol. 1999;21:409-412.